Usurious transactions in the holy Quran a study of the Effects and treatments (Journal of Misan Researches, 2023)
Usury is the increase that occurs in the sale, but not every increase, otherwise all transactions would have become prohibited, as many transactions are intended to increase the sale, and for this reason the honorable narrations divided the prohibited usury into loan usury, transactional usury or compensation usury.Many blessed verses were mentioned in the Holy Qur’an about the prohibition of usury because of its dire effects on the life of the individual and society, from consuming false money, to the economic and social disasters that pervade society if it becomes a phenomenon that is not addressed, and to the social crimes that occur to some individuals in what If they are unable to pay back their money to the usurer, it leads to class formation among the members of society.For this reason, we see that the great Islam and the Holy Qur’an dealt with usury in many verses and warned against it most severely, because in it is the loss of this world and the Hereafter, and it is zakat, as in the Almighty’s saying:(And whatever you give of usury, so that it may increase from people's wealth, it will not increase with Allah).We have dealt with this subject (usurious transactions in the Holy Qur’an, a study of effects and treatments).The second topic dealt with the treatments that it deems appropriate in limiting or eliminating usury, and this is all through the Qur’anic approach, such as education on the harms of usury, agreement in religion, urging to work in agriculture and industry, performing legal rights, and establishing Islamic banks to avoid falling into usurious transactions.